Design of a packed bed adsorber using activated carbon produced from waste coconut shells in Trinidad and Tobago - Wahid, Safiyyah N.; Maharaj, Rean; Boodlal, Donnie; Smith, Jeffrey V. (Environmental progress & sustainable energy, 2025)
Activated carbon (AC) produced from waste coconut shells in Trinidad and Tobago (TT) for utilization in a packed bed adsorber was investigated as a sustainable method for the decontamination of produced water and minimization of waste from the coconut industry. The design of the packed bed adsorber requires technical data on the phenol‐AC interaction. By utilizing information on the breakthrough performance of the laboratory‐scale fixed bed column derived from appropriate kinetic models, applicable scale‐up design protocols were then employed. It was found that the column breakthrough time increased with increasing AC bed height and increasing phenol concentration, but decreased with increasing flowrate. The bed adsorption capacity increased with bed height, achieving a maximum of 0.316 mg/g at 50% breakthrough, which occurred at 19.25 min. For the scale‐up, an adsorber of diameter 0.5 m and AC bed height of 1.7 m would be required to treat 1000 US gal/day of 2 mg/L phenol‐contaminated water. This bed height is equivalent to 219.44 kg of AC, which is produced from 1065 kg of coconut shells. This study showed that a sustainable waste management system to alleviate disposal challenges associated with produced water and the coconut industry could be implemented using the packed bed adsorber technology.